Drug-Induced Anaphylaxis in Children - Annamaria Bianchi; Rocco Valluzzi; Giuseppe Crisafulli; Paolo Bottau; Silvia Caimmi; Fabrizio Franceschini; Lucia Liotti; Francesca Mori; Sara Riscassi; Francesca Saretta; Sara Scavone; Carlo Caffarelli (Biomedicines, 2024)
Drug-induced anaphylaxis in children is less common than in adults and primarily involves beta-lactams and nonsteroidal anti-inflammatory drugs. Epidemiological studies show variable prevalence, influenced by age, gender, and atopic diseases. The pathophysiology includes IgE-mediated reactions and non-IgE mechanisms, like cytokine release reactions. We address drug-induced anaphylaxis in children, focusing on antibiotics, nonsteroidal anti-inflammatory drugs, neuromuscular blocking agents, and monoclonal antibodies. Diagnosis combines clinical criteria with in vitro, in vivo, and drug provocation tests. The immediate management of acute anaphylaxis primarily involves the use of adrenaline, coupled with long-term strategies, such as allergen avoidance and patient education. Desensitization protocols are crucial for children allergic to essential medications, particularly antibiotics and chemotherapy agents.